Cover Image, Volume 69, Issue 9. Issue 9 (9th July 2021) - Hippert, Claire; Graca, Anna B.; Basche, Mark; Kalargyrou, Aikaterini A.; Georgiadis, Anastasios; Ribeiro, Joana; Matsuyama, Ayako; Aghaizu, Nozie; Bainbridge, James W.; Smith, Alexander J.; Ali, Robin R.; Pearson, Rachael A.
Abstract : Cover Illustration: Suppressing disease‐induced upregulation of Gfap or Vimentin prevents Müller Glial hypertrophy. (See Hippert C, Graca AB, et al, https://doi.org/10.1002/glia.24034 .)